(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Introduction: Sharp weapon injuries were a common cause of death before the introduction of firearm weapons. They still cause a significant number of deaths. Sharp weapon injuries to the neck have to be differentiated as to the manner of death. Materials and Methods: 85 cases where the cause of death was due to sharp weapon injuries to the neck were studied for various parameters like age, sex and indicators of manner of death. Results: Deaths were primarily in 3rd and 4th decade of life with a male dominance. The spring season has the highest influence. An injury above the thyroid cartilage with tentative cuts and tailing was indicative of suicidal manner whereas an injury at or below the level of thyroid cartilage and involving the cervical vertebrae indicated homicidal manner of death.